Freedom from the Metaphysics of Thought to the Phénoménologie of Political Action by Hannah Arendt - mekki, fatima; maghoura, djelloul (Journal of Social Sciences and Humanities, 2022)
The present study is intended to be a philosophical study covering a certain period characterized by specific circumstances and political climate, in the sense of consecrating thought and need to resort to philosophy. This is in line with the opinion of the German philosopher Hannah Arendt, who made thought more than a necessity in order to get humanity out of the evil of unjust policies that have reduced man to a species deprived of its emotional or conscious characteristics. The essential mission of the philosopher is to bring humanity out of a state of violence towards a state of freedom and real democracy in which human rights are preserved by the constitution of each country aspiring to a State of Rights. It is in this register that fall the aims of the philosopher Arendt who lived the tortures of Nazism and its policy against the Jews displaying a contemptuous attitude towards them by the Nazist doctrine led by Adolf Hitler. The latter consecrated all policies of violence including the holocaust which embodies the most terrible of these crimes. Within this context, the philosopher raised her pen in order to shake her thought in the midst of political theory, putting the primary objective of political action, the freedom and dignity of the human being and the liberation of humanity of theories laden with megalomania. Her ideas have had an effect on the political leaders who have eradicated such deviant tendencies as destruction, narcissism, paranoia and hegemony in the application of their policies and their psychopathological thinking. Thus, thinkers in general find themselves challenged especially Arendt since she belongs to the circle of political theory, which in her research has valued the role of political institutions and public participation in the establishment of the philosophy of rights, and the consecration of the principle of freedom as the first and last objective of politics.